EFFECT OF MYOFUNCTIONAL THERAPY ON CHANGE OF OROFACIAL MUSCLE TONE IN CHILDREN WITH BITE DISTURBANCES - Lykhota, Kostiantyn; Shcherbyna, Tetyana (Eastern Ukrainian Medical Journal, 2024)
In recent years, dentistry has made significant progress in all directions, but the problem of correcting maxillofacial anomalies remains relevant to this day. Harmful environmental factors and urbanization cause an increase in endogenous and exogenous factors of dental and jaw anomalies. Complications of intrauterine development, infectious diseases, disorders of phosphorus-calcium metabolism, children’s bad habits, growth of adenoid vegetations, rhinitis, hypertrophic changes of the nasal mucosa, curvature of the nasal membrane – this is an incomplete list of these factors. Experts note that between the ages of 4 and 12, anomalies of the maxillofacial system occupy the third place in the structure of all dental diseases. Among teenagers aged 14–16, the percentage of these anomalies remains at the level of 9.9%. These figures indicate the impossibility of self-healing and the necessity of improvements in approaches to correction. Violation of the function of external breathing is one of the important factors that causes a whole cascade of pathological changes. The tongue occupies a low posterior position, in which it cannot resist the force of the buccal masticatory muscles, which narrows the jaws from the sides, moves the teeth to the frontal areas, contributes to the displacement of the lower jaw backward, and the upper jaw grows downward and has insufficient growth in the sagittal direction. These changes lead to the formation of mesial occlusion, abocclusion, deep overbite and crossbite. We set a goal to improve the treatment process of children and adolescents with abocclusion and to analyze the results of treatment with standard myofunctional devices of the EF line system in combination with a set of myogymnastics exercises with regard to the condition of the maxillofacial system and restoration of the strength of the masticatory muscles. Materials and methods. We examined children and adolescents aged 5–14 years. Patients were divided by age into three subgroups: the first: 5–8 years at the stage of early transitional dentition, the second: 9–12 years – late transitional dentition, and the third: 13–14 years of formed permanent dentition (with no formed primordia of the third permanent molars in the dental arch). Patients underwent orthopantomography. Electromyography was used to determine the strength of the circular muscle of the mouth. Results. On the orthopantomogram of patients who underwent treatment with standard functional EF Line devices in combination with myogymnastics exercises to strengthen the orbicularis oculi muscle, the recovery of the abnormal bite towards the physiological one, with the recovery of the occlusion of the front teeth, was noted. These electromyogram data showed an increase in the amplitude of the biopotentials of the orbicularis oculi muscle after the treatment. The obtained indicators according to the data of statistical processing had a high degree of significance. Conclusions. Our myofunctional therapy with the use of standard functional EF Line devices in combination with myogymnastics exercises to strengthen the circular muscle of the mouth demonstrated the restoration of the physiological bite. And the data of electromyography demonstrated the restoration of the strength of contractions of the circular muscle of the mouth.